The Fisheries Economy in the Mahakam River: Benefits and Factors that Affect It - Auliansyah Auliansyah; Yesi Aprianti; Andra Sulindrina (Faculty of Fisheries and Marine Science, Brawijaya University, 2021)
This study combines input variables and natural influences to measure fishing yields as productivity. The research was conducted in the central area of the Mahakam River watershed. The purpose of this study is to calculate the income of fishermen at each level of tidal levels and to analyse what factors that affect fisheries productivity. The research uses a mixed method analysis. The data used are primary data obtained by using a structured interview technique through a questionnaire to fishermen who live in the research location, the sampling technique of respondents using the purposive sampling technique. Data were analysed using profit analysis techniques and multiple linear regression. The results of the data analysis show that the highest profit for fishermen is when the conditions of the highest tide go to the lowest tide. Significantly, the fishermen's catch is influenced by two factors, namely the fishing location and their experiences.